Purification of PEDOT:PSS by Ultrafiltration for Highly Conductive Transparent Electrode of All‐Printed Organic Devices. Issue 46 (7th October 2016) - Kim, Soyeon; Sanyoto, Bernardi; Park, Won‐Tae; Kim, Seyul; Mandal, Saumen; Lim, Jong‐Choo; Noh, Yong‐Young; Kim, Jung‐Hyun
Abstract : A highly conductive, air stable and scalable poly(3, 4‐ethylenedioxythiophene) (PEDOT): poly(4‐styrenesulfonate) (PEDOT:PSS) are prepared by using mass production ultrafiltration. By effectively removing excess PSS and various reaction impurities using repeated 100 nm pore membrane filtration, purified PEDOT:PSS exhibit conductivity as high as 2000 S cm −1 .